Comparison of Pediatric and General Emergency Medicine Practice Patterns in Infants With Fever. (March 2015) - Vanguru, Leelasri; Redfern, Roberta E.; Wanjiku, Stephen; Sunallah, Rami; Mukundan, Deepa; Vemuru, Lakshmi
Objectives: To evaluate and compare the management approaches of pediatric and general emergency medicine physicians in infants presenting to the emergency department (ED) with complaint of fever.Methods: Infants 90 days of age or younger with a chief complaint of fever were included for review. Vital signs, laboratory workup, disposition, and final diagnosis were collected. Compliance with guidelines was assessed and compared between EDs.Results: Compliance with admission guidelines was not significantly different in any of the 3 age groups evaluated between the pediatric and general ED (PED and GED). Compliance with guideline recommendations for laboratory workup was not significantly different between the 2 EDs, nor was overall compliance with guideline recommendations.Conclusions: No significant variations in the management of febrile infants or compliance with published guidelines between PED and GED physicians were observed. Young infants can be safely treated for fever in the PED or GED.